Stalactite Cavern - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Illustration depicting an exterior view of a stalactite cavern.
Keywords: Scientific illustration; Science--Study and teaching; Chemistry; Caves; Stalactites and stalagmites; Carbon dioxide